Quality of work life and job satisfaction of LPTK employees in pekanbaru: a comparative study - Fitri Eliya; Feri Aulia Ur Rahman; Eli Sabrifha (JPGI (Jurnal Penelitian Guru Indonesia), 2026)
Quality of Work Life and Job Satisfaction of employees are two important interrelated aspects of the workplace. This study was conducted to determine the differences in Quality of Work Life and Job Satisfaction of Employees Working at Pekanbaru's LPTK (Teaching and Training Institutions). The study population was employees or educational staff working at the LPTK of Riau University and Sultan Syarif Kasim State Islamic University of Riau. The research approach used a comparative quantitative approach, involving 76 respondents. The data collection technique used a Likert scale. The collected data were analyzed using an Independent Sample t-test. The results show differences in the levels of Quality of Work Life and Job Satisfaction between LPTK employees working under the auspices of the Ministry of Education, Culture, Research, and Technology and LPTK employees working under the auspices of the Ministry of Religious Affairs, specifically regarding their status and personnel system. Overall, both Quality of Work Life and Job Satisfaction in both groups were still in the moderate category. These results indicate the need for improvements to the system and welfare of non-civil servant employees to make them more proportional and performance-based.